SENSORY EVALUATION OF CAPE GOOSEBERRY (Physalis peruviana L.) COLOMBIAN ECOTYPE IMPREGNATED WITH NATIVE STRAIN Lactobacillus plantarum LPBM10 AND COMMERCIAL STRAIN Lactobacillus casei ATCC 393 - MARÍN A., Zaira T T; CORTÉS R., Misael; MONTOYA C., Olga I. (Vitae, 2010)
Sensory evaluation is one of the most important tools in new food development, such as fruits with probiotic microorganisms. Bacteria like L. plantarum and L. casei show beneficial health effects in people consuming them. This investigation evaluates the sensory attributes of cape gooseberry inoculated with the strains L. plantarum and L. casei using the vacuum impregnation process as incorporation mechanism in the fruit. A 14% p/p glucose solution inoculated with lactobacilli in a concentration of 5 in a McFarland scale is used as the liquid of impregnation. Tests scalars descriptive of 9 blocks are applied to the samples. The judges evaluate the biggest or smallest intensity in the qualified attribute with regard to the control sample, which was fresh cape gooseberry under the same storage conditions (temperature and time) that the impregnated samples. In general, the results established by the trained panel show that impregnated cape gooseberry are sweeter, more juicy, more translucent, more orange-coloured, less acid and less harsh.